NETQUANT: Automated Quantification of Neutrophil Extracellular Traps - Mohanty, Tirthankar; Sørensen, Ole E.; Nordenfelt, Pontus (Frontiers in Immunology, 2018)
Neutrophils can eject extracellular traps (NETs) that are extensive webs of DNA covered with antimicrobial proteins into the extracellular environment during infection or inflammation as a part of their defense arsenal. Image acquisition of fluorescently labeled NETs and subsequent image-based quantification is frequently used to analyze NET formation (NETosis) in response to various stimuli. However, there are important limitations in the present methods for quantification. Manual methods tend to be error-prone, tedious and often quite subjective, whereas the software-rooted options are either semi-automatic or difficult to operate. Here we present an automated and uncomplicated approach for quantifying NETs from fluorescence images, built as a freely available app for MATLAB®. It is based on detection of a set of clearly defined parameters, all related to the biological manifestation of NETs and allowing for single-cell resolution quantification and analysis.